Speedy Bus Mastering PCI Express - Bittner, Ray (22nd International Conference on Field Programmable Logic and Applications (FPL 2012), 2012)
PCI Express is a ubiquitous bus interface providing the highest bandwidth connection in the PC platform. Sadly, support for it in FPGAs is limited and/or expensive. The Speedy PCIe core addresses this problem by bridging the gap from the bare bones interface to a user friendly, high performance design. This paper describes some of the fundamental design challenges and how they were addressed as well as giving detailed results. The hardware and software source code are available for free download from [12].